Nucleotide sequence, tissue-specific expression, and chromosome location of human carbonic anhydrase III: the human CAIII gene is located on the same chromosome as the closely linked CAI and CAII genes. - Wade, R (1986)
The carbonic anhydrases (CA) are a class of metalloenzymes that catalyze the reversible hydration of carbon dioxide. The genes for the carbonic anhydrase isozymes are members of a multigene family that are differentially expressed in a number of cell types. We have isolated a full-length representative of a CAIII mRNA transcript from an adult human muscle cDNA library, and we present the complete nucleotide sequence of this cDNA clone. RNA blots demonstrate that CAIII messages can be detected in a variety of cell types but that high-level expression is limited to human fetal and adult skeletal muscle and to rodent slow skeletal muscle and liver. In addition, we have used a panel of human-mouse cell hybrids to localize the human CAIII gene to chromosome 8. Previous reports have established the CAI and CAII isozyme genes to be closely linked on chromosome 8, and the assignment of the CAIII gene to the same chromosome raises the possibility that these genes may all be linked at a single complex locus.